DINAMIKA PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Srimin Pinem; Rizkan Zulyadi; muhammad yusrizal adi syaputra (Jurnal Yuridis, 2023)
The debate on eradicating criminal acts of corruption for criminal law reform is legal and theoretical. This article discusses an important aspect of eradicating criminal acts of corruption in criminal law reform, namely how the position of the law applied in criminal law reform is seen in society from a legal theory perspective since the passing of the New Criminal Code in Indonesia. This problem was analyzed theoretically using normative legal research methods and the conclusion was obtained that the dynamics of eradicating corruption in Indonesia since the enactment of the New Criminal Code will experience a slowdown in the law enforcement process. This is because there are several articles that do not have firmness and legal certainty, such as article 603 of the new Criminal Code which reduces the sentence period for corruptors. The New Criminal Code has made corruption offenses the same as general offenses, so that they no longer have special characteristics or fall into the category of special crimes. Therefore, the Government should review the articles related to corruption offenses in the New Criminal Code so that the legal regulations do not experience a setback compared to the Corruption Eradication Law. Apart from that, there must be synchronization of regulations between the New Criminal Code and Law Number 30 of 2001 concerning the Eradication of Corruption Crimes.